Antiapoptotic efficacy of seed of Eugenia jambolana on testicular germ cell in experimental diabetic rat: a genomic study. (3rd June 2015) - Ghosh, A.; Jana, K.; Pakhira, B. P.; Ghosh, D.
Summary: This study was designed to focus the genetic regulation of diabetes‐induced testicular hypofunction and its amelioration by ethyl acetate fraction of seed of Eugenia jambolana . In this regard, we have assessed relevant biosensors such as biochemical, spermiological, histological and gene expression of antioxidant enzymes, germ cell apoptosis and androgenic key enzymes along with in situ end labelling and DNA fragmentation study. After 60 days administration of said fraction, significant recovery in the glycated haemoglobin, serum testosterone, sperm viability, hypo‐osmotic swelling and nuclear chromatin decondensation were noted in fraction‐treated diabetic group in comparison with diabetic control. Besides this, a significant recovery in the expression of Bax, Bcl‐2, caspase‐9, caspase‐3, catalase, peroxidase, ∆ 5, 3β‐hydroxy steroid dehydrogenase and 17β‐hydroxy steroid dehydrogenase genes was noted towards the control in ethyl acetate fraction‐treated group. Testicular histology focused a significant recovery in the number of different generation of germ cells at stage VII of spermatogenesis in fraction‐treated group. In situ end labelling and DNA fragmentation study of testicular tissues also showed a significant recovery in fraction‐treated group towards the control. These findings indicate that the ethyl acetate fraction showed outstanding antiapoptotic activity by neutralising oxidative stress as well as by the improvement in glycaemic sensors.